2012
DOI: 10.1042/bst20110772
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic clustering of IP3 receptors by IP3

Abstract: The versatility of Ca2+ as an intracellular messenger stems largely from the impressive, but complex, spatiotemporal organization of the Ca2+ signals. For example, the latter when initiated by IP3 (inositol 1,4,5-trisphosphate) in many cells manifest hierarchical recruitment of elementary Ca2+ release events ('blips' and then 'puffs') en route to global regenerative Ca2+ waves as the cellular IP3 concentration rises. The spacing of IP3Rs (IP3 receptors) and their regulation by Ca2+ are key determinants of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…We liken this to channel clustering. Both RyRs and IP 3 Rs form clusters, and such an arrangement is thought to be important for coordinating channel activity, particularly for RyR during excitation-contraction coupling (Rahman, 2012;Schendel et al, 2012). Interestingly, a uniform increase in TPC density also has a broadening effect on the concentration-effect relationship (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…We liken this to channel clustering. Both RyRs and IP 3 Rs form clusters, and such an arrangement is thought to be important for coordinating channel activity, particularly for RyR during excitation-contraction coupling (Rahman, 2012;Schendel et al, 2012). Interestingly, a uniform increase in TPC density also has a broadening effect on the concentration-effect relationship (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…5A, the average of PA in the FIPI+ FERT group was 1.22 versus 1.02 ng in the egg, but these values were not significantly different). A small amount of PA may produce a small increase in [Ca] i that would be amplified through calcium-induced calcium release which could involve [Ca] i activation of PLC (Rhee, 2001; Stith et al, 1993) or IP3 receptors (Larabell and Nuccitelli, 1992; Larabell et al, 2004; Miyazaki, 2006; Rahman, 2012; Shuai et al, 2007). As another source of PA, we have found that sperm contain PA (W. Holland and B. Stith, unpublished) and treatment of the egg with FIPI or 1-butanol would not affect sperm PA.…”
Section: Discussionmentioning
confidence: 99%
“…The intervening region is referred to as the regulatory or coupling domain and structure/function studies have revealed important insights into how IP3 binding at the N-terminal region leads to channel opening in the C-terminal region (11). There is evidence to suggest that the IP3Rs are arranged in the ER membrane in a nonrandom distribution and that dynamic clustering of these receptors may be functionally important (12,13). Phosphorylation and dephosphorylation of the IP3R also regulates Ca 2+ flux through this channel (14), but it remains to be determined whether the IP3R is regulated by other posttranslational modifications.…”
mentioning
confidence: 99%